Effect of Spiritual Emotional Freedom Technique (SEFT) on Pain During the COVID-19 Pandemic - Mulianda, Dwi; Ropyanto, Chandra Bagus (Scripta Medica, 2024)
Background/Aim: Effective pain management has become more difficult during the COVID-19 pandemic. The spiritual emotional freedom technique (SEFT) can be one of the efforts to overcome acute and chronic pain because SEFT is an intervention that can overcome physical problems by combining spiritual and psychological energy through sincerity of prayer and surrender. Aim of this study was to analyse the effect of SEFT on pain during the COVID-19 pandemic and the difference in the effect of SEFT on pre- and post-intervention pain.Methods: The research method was a quasi-experiment with a pre-post-test group design. The study was conducted by assessing the pain scale before and after using the numeric rating scale (NRS). The sample size in the study was 98 respondents. Inclusion criteria were: patients experiencing acute or chronic pain, composed consciousness, being able to communicate well enough and being consistent with the stages of intervention. Exclusion criteria were, unconsciousness, patients diagnosed with COVID-19, shortness of breath, cognitive impairment and hearing loss.Results: Pain measured by NRS in respondents for the pretest was 2.40 (1.679) and the post-test was 1.39 (0.490) with the interpretation of mild pain. Pretest and post-test on respondents showed significant pain reduction (Wilcoxon test, p = 0.0001; Mann Whitney test, p = 0.013).Conclusion: Respondents experienced less pain after SEFT than before the intervention. The impact of the pain scale on respondents was different before and after SEFT.